Economic burden of influenza illness among children under 5 years in Suzhou, China: Report from the cost surveys during 2011/12 to 2016/17 influenza seasons. Issue 8 (22nd February 2021) - Wang, Yin; Chen, Liling; Cheng, Fangfang; Biggerstaff, Matthew; Situ, Sujian; Zhou, Suizan; Gao, Junmei; Liu, Changpeng; Zhang, Jun; Millman, Alexander J.; Zhang, Tao; Tian, Jianmei; et al.
Highlights: We assessed economic burden of influenza in children <5 in Suzhou from 2011-2017. Cost per illness episode was 161 for outpatient and 1426 for hospitalization. Annual economic burden of influenza among children <5 in Suzhou was 7.4 million. Indirect costs accounted for 22-36% of the total annual economic burden. Influenza in children <5 in Suzhou results in a substantial annual economic burden. Abstract: Background: Data are limited on the economic burden of seasonal influenza in China. We estimated the cost due to influenza illness among children < 5-year-old in Suzhou, China. Methods: This study adopted a societal perspective to estimate direct medical cost, direct non-medical cost, and indirect cost related to lost productivity. Data to calculate costs and rates of three influenza illness outcomes (non-medically attended, outpatient and hospitalization) were collected from prospective community-based cohort studies and hospital-based enhanced laboratory-confirmed influenza surveillance in Suzhou during the 2011/12 to 2016/17 influenza seasons. We used mean cost-per-episode, annual incidence rates of episodes of each outcome, and annual population size to estimate the total annual economic burden of influenza illnesses among children < 5-year-old for Suzhou. All costs were reported in 2017 U.S. dollars. Results: The mean cost-per-episode (standard deviation) was 9.92 (13.26) for non-medically attended influenza, 161.05 (176.98) for influenza outpatient illnesses, and 1425.95 (603.59) for influenza hospitalizations. By applying the annual incidence rates to the population size, we estimated an annual total of 4, 919 episodes of non-medically attended influenza, 21, 994 influenza outpatient, and 2, 633 influenza hospitalization. Total annual economic burden of influenza to society among children < 5-year-old in Suzhou was 7.37 (95% confidence interval, 6.9–7.8) million, with estimated costs for non-medically attended influenza of 49, 000 (46, 000–52, 000), influenza outpatients 3.5 (3.3–3.8) million, and influenza hospitalizations 3.8 (3.6–3.9) million. Among outpatients, the indirect cost was 36.3% (1.3 million) of total economic burden, accounting for 21, 994 days of lost productivity annually. Among inpatients, the indirect cost was 22.1% (829, 000), accounting for 18, 431 days of lost productivity annually. Conclusions: Our findings show that influenza in children < 5-year-oldcauses substantial societal economic burden in Suzhou, China. Assessing the potential economic benefit of increasing influenza vaccination coverage in this population is warranted.